2021
DOI: 10.3390/rs13173416
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variations in Terrestrial Water Storage with Variable Forces across the Yellow River Basin

Abstract: Terrestrial water storage (TWS) variations are a result of the interconnected impact of various variables including climate, hydrology, ecology, and anthropogenic activities. Previous studies have indicated that climate factors (e.g., precipitation and potential evapotranspiration), vegetation restoration, and water withdrawals (irrigational and industrial water use) are the major determinants of TWS depletion across the Yellow River Basin (YRB). However, few studies have provided explicit information about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Some studies [59,60] show that the water consumption function of vegetation in arid and semi-arid areas exceeds the water storage function. Zhou et al [61] show that the water consumption function of vegetation in the Loess Plateau is dominant. This is consistent with the result that the change in water reserves is negatively correlated with NDVI in a large area.…”
Section: Main Influencing Factor Of Twsmentioning
confidence: 99%
“…Some studies [59,60] show that the water consumption function of vegetation in arid and semi-arid areas exceeds the water storage function. Zhou et al [61] show that the water consumption function of vegetation in the Loess Plateau is dominant. This is consistent with the result that the change in water reserves is negatively correlated with NDVI in a large area.…”
Section: Main Influencing Factor Of Twsmentioning
confidence: 99%
“…However, there was a notable decreasing trend of −2.76 mm/yr from 2004 to 2015. Zhou et al (2021) demonstrated a declining trend in TWS across the Yellow River Basin in northern China, with rates ranging from −3.8 mm/yr to −6.6 mm/yr, as determined by the analysis of GRACE satellite data. Additionally, the study highlighted the significant influence of minimum temperature and runoff on the variations in TWS (Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Zhou et al (2021) demonstrated a declining trend in TWS across the Yellow River Basin in northern China, with rates ranging from −3.8 mm/yr to −6.6 mm/yr, as determined by the analysis of GRACE satellite data. Additionally, the study highlighted the significant influence of minimum temperature and runoff on the variations in TWS (Zhou et al, 2021). Bahrami et al (2020) indicated the significant role of SWE in TWS variation, using multisource remote sensing and the Water‐Global Assessment and Prognosis Global Hydrology Model (WGHM) in Canada from 2002 to 2011.…”
Section: Introductionmentioning
confidence: 97%